2011
DOI: 10.1504/ijgw.2011.044403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the solid content on biogas production from Jatropha curcas seed cake

Abstract: Anaerobic conversion of Jatropha curcas seed cake was studied in a five-litre working volume batch reactor at 30°C. Over a 60-day operating period, a slurry of seed cake in water at a 1 : 20 seed cake-to-water ratio showed the highest methane yield of 296 litre methane/kg Chemical Oxygen Demand (COD) degraded (or 156 litre/kg of Jatropha curcas seed cake added) and achieved 52% COD removal. The results revealed that Jatropha curcas seed cake treated anaerobically can be a good source of methane, with optimal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…For seed bagasse, one research observed 5.6% moisture, while another reported 10% [42]; the first value is close to 4.4% reported in this paper, the difference may be due to the method of extraction of the oil since for this research it was performed by mechanical extraction, while the authors performed by Soxhlet. Data of the bagasse of oil seeds belonging to the Euphorbiaceae family have also been carried out and are similar to those determined in this research, an example is the 7.5% moisture obtained on the bagasse of the seed of Jatropha curcas [43] or 8.3% achieved with the same substrate [44], most of these studies are only done on the bagasse of the seed (and not on the aerial parts of the plant) because it is the raw material for the extraction of the oil. In relation to TS, FS and VS for BSRc, 92.7% and 5.6% were achieved, respectively; but no VS determined [42], values decreased by 3 and 77% compared to those shown in Table 2.…”
Section: Discussionsupporting
confidence: 72%
“…For seed bagasse, one research observed 5.6% moisture, while another reported 10% [42]; the first value is close to 4.4% reported in this paper, the difference may be due to the method of extraction of the oil since for this research it was performed by mechanical extraction, while the authors performed by Soxhlet. Data of the bagasse of oil seeds belonging to the Euphorbiaceae family have also been carried out and are similar to those determined in this research, an example is the 7.5% moisture obtained on the bagasse of the seed of Jatropha curcas [43] or 8.3% achieved with the same substrate [44], most of these studies are only done on the bagasse of the seed (and not on the aerial parts of the plant) because it is the raw material for the extraction of the oil. In relation to TS, FS and VS for BSRc, 92.7% and 5.6% were achieved, respectively; but no VS determined [42], values decreased by 3 and 77% compared to those shown in Table 2.…”
Section: Discussionsupporting
confidence: 72%
“…Methane yield: 156 L/kg of seed cake; COD removal: 52%. [91] Jatropha seed cake Semi-continuous flow at 30 • C; COD range: 1.25-5 kg/m 3 day.…”
Section: Conditions Resultsmentioning
confidence: 99%
“…Sinbuathong et al [91] showed that J. curcas seed cake is a good source of methane by anaerobic digestion. Methane yields of up to 156 L/kg cake can be achieved, and the optimal cake-to-water ratio is in the range of 1:10-1:20.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…Mesocarp, as opposed to the cake, is not well degradable. However, mesocarp could have significant value for biogas production and increase biogas yields in a powerplant Mesocarp yield is roughly 200 m 3 •t −1 [28]. When both Jatropha curcas cake and adequate amount of Jatropha curcas mesocarp (adequate portion from collected fresh fruit bunches) are processed into biogas, it would be approximately 310 m 3 •t −1 [35].…”
Section: Literature Reviewmentioning
confidence: 99%